Modos de aprendizaje en los contextos actuales para mejorar el proceso de enseñanza (2021)
Learning is a subject of constant concern for all those dedicated to this activity, where there are different paradigmatic approaches. The objective of this work is to assess the different types of learning associated with current contexts in order to improve the teaching-learning process. The fundamental methods used have been, from the theoretical, the logical historical and the synthetic analytic; and from empyrean, observation and analysis of documents. The main results are associated with the description of the most useful methods in these times, the psychological current that underlies each one of them, their complementary elements and adaptations (whether virtual or face-to-face) to the generation that today is in the classrooms. With the assessment of the different learning concepts, a tool has been provided to support the work of teachers of these times